2004
DOI: 10.1074/jbc.m408725200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Engagement of FcϵRI and CC Chemokine Receptor 1 on Mast Cell Activation and Motility

Abstract: Mast cells and basophils play an important role in IgEassociated allergic disorders and immune responses to parasites. Fc⑀RI cross-linking is a key event in the activation of mast cells and basophils. The Fc⑀RI is composed of three subunits: an ␣ chain, a ␤ chain, and a pair of ␥ chains, joined by a disulfide bond. The association of allergen with IgE bound to Fc⑀RI induces the transphosphorylation of cytoplasmic domains in the ␤-and ␥-chains called immunoreceptor tyrosinebased activation motifs via Lyn activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 32 publications
5
46
0
Order By: Relevance
“…CCL3 was reported to stimulate human mast cell degranulation in vitro (16) and murine mast cell degranulation in vitro and in vivo (7,17). We found that treatment of mast cells with CCL3 and Ag results in greater degranulation than does cross-linking of FcεRI alone (8,17). Mice in which CCL3 is deficient or neutralized fail to display typical allergic symptoms after ocular exposure to allergen.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…CCL3 was reported to stimulate human mast cell degranulation in vitro (16) and murine mast cell degranulation in vitro and in vivo (7,17). We found that treatment of mast cells with CCL3 and Ag results in greater degranulation than does cross-linking of FcεRI alone (8,17). Mice in which CCL3 is deficient or neutralized fail to display typical allergic symptoms after ocular exposure to allergen.…”
mentioning
confidence: 63%
“…Because CCL7 is a ligand for CCR1, we examined whether CCL7 could stimulate CCR1 and contribute to mast cell activation in a manner similar to that observed for another ligand, CCL3 (8). RBL-CCR1 cells and BMMCs derived from wild-type mice, which both display characteristics of mucosal-type mast cells, express CCR1; RBL-CCR1 cells express CCR1 but no other CCRs, whereas BMMCs cultured with stem cell factor express CCR1-5 (43).…”
Section: Ccl-7 and Ag Synergistically Induce Degranulation In Rbl-ccrmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, CCL3 synergistically enhanced Fc⑀RI-mediated degranulation and gene expression of cytokines and chemokines (e.g. IL-6 and CCL7/MCP-3) in a rat basophilic leukemia 2H3 cell line (RBL-2H3) expressing CC chemokine receptor 1 (CCR1), a receptor for CCL3, and bone marrow-derived murine mast cells (11)(12)(13)(14). These observations indicate that (i) the simultaneous engagement of Fc⑀RI and CCR1 is important for optimal activation of mast cells in vitro and physiologically relevant levels of mast cell activation in vivo, and (ii) there is a cross-talk between the Fc⑀RI-mediated and CCR1-mediated signaling cascades.…”
mentioning
confidence: 99%